Arte contemporáneo una mirada crítica a la simbología precolombina. - Moreno Vaca, Roció Piedad (2016)
3533/5000 Speaking of the history of our ancestral roots, takes us on a journey back to time, allows us to venture into the poetry of his remains, between designs and finds, as yet undiscovered history. It is art and the passion for history that allows us to contribute with a small part of research the meaning of our first discoveries that describe what we are today. In the next research on the artistic object as a symbolic strategy for the strengthening of our cultural identity, we will see how we have unconsciously adopted patterns of identity that do not belong to us, several reasons afflicting a society where media influence by disinformation and overwhelming programs in They force us to appropriate cultures that definitely do not belong to us, on the other hand the social networks in their misuse, are factors that distances us from reality, cultures that take away the interest weakening ours. Cultural identity is our values, pride, traditions, symbols, beliefs and modes of behavior that are part of a social group and that act so that the individuals that are part, can base their feeling of belonging. Nowadays, new artistic and avant-garde trends allow the public to be an active part of the work, so Eat Art or edible Art will serve as a support for the diffusion of the theme that symbolically develops in places of Cultural diffusion as it is the Hall of Machala and the Hall of Julio of Guayaquil. The dissemination of our cultural roots should be a reason for recognition of the institutions of culture who must create commitments to ensure the diffusion of our identity to recognize us in space and time and know where we come from, hence, Contemporary art is a Tool of artistic gesture that allows from this proposal of investigation to be opportune moment for the dialogue of belonging and recognition that has remained unknown by the collective. Now, art historically has been considered as an object of sacredness allowing to create certain barriers in the public that looks at the artistic work as something that does not allow a direct relationship, this has undoubtedly been a reason for questioning since the origin of art has A function closely related to the human being, to be a useful motive and that his presence was available to the community in acts of ritual for example. Over time, art became a tool of persuasion for economic power and little Soon became part of the large collections of these that successfully saved the triumph of his hierarchy. Today it is understood that art must be a democratizing event where social classes narrow hierarchical limits pretending to return to where art was considered a ritual gesture capable of aesthetic principles can interact with the audience that assists in an interested or disinterested way, this Means to rethink the concept of art something that in contemporary times dares to do. The document is a theoretical and artistic approach that focuses on the precolumbian Jama Coaque culture and from contemporary art disseminate some of its symbologies developed by this culture, in this aspect through Eat Art reproduces several of its symbologies in cookies that Openly distributed as snack in the aforementioned halls